From "rayanitan" to "rayaneshi" The role of grammar and Persian Language patterns in word selection - Mostafa Mousavi (مطالعات زبانی و بلاغی)
Recently, some academics have used the title "zabānshenāsi ye rāyāneshi" in the naming of academic fields. Before that, this combination was created and published in the Academy of Persian Language and Literature. In this article, the method of making the second part of this name, "Rāyāneshi", its origin and source is discussed and it is shown that this word, which is made from the Pahlavi language, Its construction is in conflict with the language rules, Persian grammar, and Persian language patterns is wrong, just as the word "rāyāne", which was created by the Academy of Iranian Language (Farhangestān II) equivalent to "computer", is wrong according to the rules of the Persian language, and although it has fewer problems than "rāyāneshi" It is acceptable due to high usage.Of course, the word "computer" was established and common in the Persian language, and there was no need to create an equivalent for it, and today it is more common than "rāyāne". In this article, it is shown that the use of "rāyāneshi" is not acceptable in any way.